INDUSTRI WISATA HALAL DI SUMATERA BARAT: POTENSI, PELUANG DAN TANTANGAN - ROZALINDA ROZALINDA; NURHASNAH NURHASNAH; SRI RAMADHAN (Maqdis: Jurnal Kajian Ekonomi Islam, 2019)
The aim of this research is to map the economic potential of the development of halal tourism in West Sumatra, and analyze the opportunities and challenges of developing halal tourism in West Sumatra. This research uses mixed methods. The location of the study was conducted in West Sumatra Province. Data collection techniques were carried out through observation, questionnaires, interviews, and documentation data. The data analysis technique uses SWOT analysis. The results of the study show that West Sumatra has a very potential halal tourist destination. Tourist attractions in West Sumatra are one of the most popular tourist destinations in Indonesia. Supported by a variety of facilities supporting the halal tourism industry including the availability of good sharia-compliant hotels, comfortable worship facilities, and the availability of halal culinary centers. Tourism is one of the contributors to local revenue sources (PAD).